Relationship between physical activities and mental health in older people: a bibliometric analysis - Zhang, Yuesen; Zhou, Mei; Yin, Zhihua; Zhuang, Wenzhen; Wang, Yufeng (Frontiers in Psychiatry, 2024)
Objective: To summarize the general situation and focal points of research on the physical activity and mental health of older people over the past 15 years and provide references for future research. Methods: Literature published between January 1, 2009, and December 31, 2023, was retrieved from the Web of Science core database. A bibliometric visualization analysis of countries/regions, institutions, authors, keywords, and references was conducted using CiteSpace6.1.R6. Results: A total of 4,329 articles were included, and the annual number of articles published over the past 15 years showed an upward trend. The articles were primarily from 65 countries/regions and 626 institutions. The most represented country and institution were the USA and the University of Pittsburgh, respectively. Among the authors identified, Schuch and Callow were the most influential. The research focuses on four areas: the psychological effects of physical activity in older people; physical activity intervention approaches to the mental health of older people; physical activity and mental health assessment questionnaires; and the impact of physical activity on multidimensional aging. Research frontiers involve emerging topics such as the assessment and intervention of mental health in older people and the relationship between their physical activity and cognitive function. Conclusion: This study conducted a comprehensive, objective, and visual analysis of publications and revealed the status of relevant studies, trending topics, and trends concerning the physical activity and mental health of older people from 2009 to 2023. We hope that this work will help researchers identify new perspectives on potential collaborators, important topics, and research frontiers.